United Nations Demographic Yearbook 2013 - United Nations (United Nations, 2014)
Demographic Yearbook 2013 is the sixty-fourth in a series published since 1948. Through the cooperation with the National Statistical Offices, official demographic statistics are compiled in the Year book, as available, for more than 230 countries and areas of the world up to the reference year 2013. This edition of the Yearbook contains chapters on the population size and distribution, the population of capital cities, fertility, foetal mortality, infant and maternal mortality, general mortality, nuptiality and divorce.